Phenomenological Study of Spiritual Experience in Individuals Experiencing Identity Crisis - Marselina, Ressa Kiki (PELNUS | Pen en Light for Natural Union of Science, 2024)
: This phenomenological study explores the lived spiritual experiences of individuals undergoing identity crises, aiming to understand how spirituality influences identity development during times of existential questioning. Drawing on in-depth semi-structured interviews with a diverse group of participants aged 18 to 40, the research identifies key themes that illuminate the complex interplay between spirituality and identity formation. Findings reveal that spiritual practices, such as meditation and prayer, serve as vital tools for navigating identity confusion, fostering self-exploration, and promoting personal growth. Additionally, participants highlighted the importance of community and belonging derived from spiritual groups, which provided essential support during their identity journeys. Transformative spiritual experiences emerged as pivotal moments that reshaped participants’ self-understanding, while the challenge of spiritual bypassing underscored the necessity for authentic engagement with emotional struggles. The study contributes to existing theories of identity development by emphasizing the role of spirituality as a resource in overcoming identity crises. Implications for clinical practice and educational settings are discussed, suggesting that incorporating spiritual exploration and community support can enhance individuals' journeys toward self-discovery and identity formation. This research highlights the profound potential of spirituality in facilitating personal transformation amid the complexities of identity development.